2007
DOI: 10.1242/jcs.004598
|View full text |Cite
|
Sign up to set email alerts
|

Cellular prion protein (PrPC) protects neuronal cells from the effect of huntingtin aggregation

Abstract: The effect of normal cellular prion protein (PrPC) on abnormal protein aggregation was examined by transfecting huntingtin fragments (Htt) into SN56 neuronal-derived cells depleted of PrPC by RNA interference. PrPC depletion caused an increase in both the number of cells containing granules and the number of apoptotic cells. Consistent with the increase in Htt aggregation, PrPC depletion caused an decrease in proteasome activity and a decrease in the activities of cellular defense enzymes compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…Crosstalk between PrP and other neurodegenerative disease causing proteins is not limited to AD, as another report has suggested that PrP protects against polyglutamine aggregate toxicity. 40 Tau, our study there was not a significant progressive rotarod deficit in α-synuclein Tg + mice or that the repeated testing had a masking effect on this phenotype ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 46%
“…Crosstalk between PrP and other neurodegenerative disease causing proteins is not limited to AD, as another report has suggested that PrP protects against polyglutamine aggregate toxicity. 40 Tau, our study there was not a significant progressive rotarod deficit in α-synuclein Tg + mice or that the repeated testing had a masking effect on this phenotype ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 46%
“…Plasmids encoding V5-tagged hNaa15p, hNaa25p, and hNaa35p were previously described (4,39,40). Plasmids encoding Huntingtin polyQ-enhanced green fluorescent protein (EGFP) fusion proteins (pHttQ25-EGFP, pHttQ72-EGFP, and pHttQ103-EGFP) (24,46) were generously provided by Evan Eisenberg, National Heart, Lung and Blood Institute, Bethesda, MD. Plasmids encoding EGFP-Huntingtin polyQ fusion proteins (pEGFP-HttQ23 and pEGFP-HttQ74) (45) were generously provided by David C. Rubinsztein, University of Cambridge, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…While suggested roles for PrP C include cell signaling, differentiation and adhesion, an increasing number of studies have implicated PrP C in neuroprotection against oxidative stress, ischemia and toxic protein aggregation. [27][28][29][30][31][32][33][34][35][36]38,46 Given the proposed neuroprotective role for PrP C , low levels of PrP C in CSF following spinal cord injury may well create a window in which neurons are susceptible to damage. CSF reduction in PrP C following spinal cord injury is specific (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions PrP C is released from cells into the CSF. [22][23][24][25][26] We evaluated PrP C in CSF samples for two reasons: First, PrP C has been hypothesized to be neuroprotective [27][28][29][30][31][32][33][34][35][36][37][38] and it follows that changes in CSF PrP C expression levels might influence neural cell survival. Secondly, CSF from some CJD patients is infectious 39 and changes in the CSF levels of PrP C may well alter the rate of PrP Sc replication.…”
mentioning
confidence: 99%